COVID-19 Affects Everyone but Not Equally : The Gendered Poverty Effects of the COVID-19 Pandemic in Colombia - Cuesta, Jose; Pico, Julieth (World Bank, Washington, DC, 2020)
COVID-19 (Coronavirus) does not distinguish borders, race or gender. Everyone is affected but not equally. Women are at risk of seeing structural socioeconomic gaps deepen with COVID-9(Coronavirus), along with worsening violence and social norms. The authors explore the extent to which COVID-19 (Coronavirus) will exacerbate gendered employment, income generation and, ultimately, poverty gaps. The authors explore a new but sprawling literature discussing the employment effects of COVID-19 (Coronavirus). The authors also develop a simple microsimulation methodology to estimate the poverty impacts of COVID-19 (Coronavirus) (versus a counterfactual of no COVID-19 (Coronavirus)); the specific poverty reduction impacts of mitigation policies; and the distinctive impacts by gender. The authors test our microsimulation approach in Colombia, a country that has implemented an unparalleled number of mitigation measures and has reopened its economy earlier than regional neighbors. The authors find that the poverty impacts of COVID-19 (Coronavirus) are daunting (between 3.0 and 9.1 pp increases of poverty headcount). Mitigation measures vary considerably in their individual capacity to reverse poverty (from no effect to 0.9 pp poverty reduction). A fiscally neutral universal basic income (UBI) will bring about larger poverty reductions. Importantly, both men and women report similar poverty impacts from the pandemic and mitigation policies. The sheer magnitude of the downturn, the design of interventions and our own measure of poverty explain this results.